Pengaruh Gaya Hidup dan Motivasi Konsumen Terhadap Keputusan Pembelian di Alun-Alun Coffee, Rawamangun - Dody Yudha Saputra; Harry Sardjono (UNIVERSITAS KALBIS, 2022)
This study aims to determine how much influence the lifestyle and motivation of consumers on purchasing decisions at the Alun-Aloun Coffee, Rawamangun. This research is a quantitative study using SPSS Statistics 22 program with a total sample of 100 respondents who are residents of Jabodetabek who have bought product at Alun-Alun Coffee using nonprobability sampling and purposive sampling techniques. The results of this study indicate that the lifestyle has a significant effect on purchasing decisions with a value of 1,986 greater than 1,660 and consumer motivation has a significant effect on purchasing decisions with a value of 9,130 greater than 1,660. The benefit of this research for Alum-Alun Coffee is as input or evaluation material in order to continue to improve product quality to be able to maintain the lifestyle and motivation of consumers so that Alun-Alun Coffee can compete with other competitors.